2020
DOI: 10.5187/jast.2020.62.2.208
|View full text |Cite
|
Sign up to set email alerts
|

The impact of short-term acute heat stress on the rumen microbiome of Hanwoo steers

Abstract: Heat stress negatively affects cattle productivity by reducing feed intake. In the present study, we assessed if the rumen microbiome composition of Hanwoo steers was altered by exposure to heat stress. Rumen samples were collected from four Hanwoo steers that were individually housed in climate-controlled chambers with 60% humidity and environmental temperatures of: 1) 15℃ (0-day group), 2) 35℃ for 3 days (3-day group), and 3) 35℃ for 6 days (6-day group). The total community DNA of samples was extracted, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
24
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 24 publications
10
24
2
Order By: Relevance
“…This phylum was already reported as significant in heat stress analysis of pigs reported by He [37]. Chloroflexi and Planctomycetes significantly associated with rectal temperature were also reported as a significant phyla in the analysis of short-term acute heat stress on the rumen microbiome of Hanwoo steers [33].…”
Section: Discussionsupporting
confidence: 52%
“…This phylum was already reported as significant in heat stress analysis of pigs reported by He [37]. Chloroflexi and Planctomycetes significantly associated with rectal temperature were also reported as a significant phyla in the analysis of short-term acute heat stress on the rumen microbiome of Hanwoo steers [33].…”
Section: Discussionsupporting
confidence: 52%
“…The higher abundance of R. bromii in winter suggests higher amylolytic activity through their preferential growth in the rumen, which might be attributed to higher VFA production in winter. Baek et al [ 83 ] revealed that heat stress reduced the abundance of fibrolytic Ruminococcaceae while increasing the lactate-producing Lactobacillaceae and amylolytic Prevotella and Ruminobacter in Hanwoo steers. Likewise, Zhao et al [ 84 ] reported that heat-stressed dairy cows had a significantly higher relative abundance of Streptococcus , unclassified Enterobacteriaceae , Ruminobacter , Treponema , and unclassified Bacteroidaceae.…”
Section: Discussionmentioning
confidence: 99%
“…The modern poultry genotypes are more susceptible to HS due to marked growth rate along with greater metabolic activity [ 1 ]. An earlier study with the use of a culture technique showed that the number of Enterobacteriaceae was decreased, whereas Streptococcus and Staphylococcus numbers were increased by HS in the small intestine of chickens [ 29 ]. Microbial community composition in the ileum and cecum of chickens was also altered by heat exposure to 30°C for 24 h [ 12 ].…”
Section: Microbiota Changes In the Gut By Heat Stressmentioning
confidence: 99%